1998
DOI: 10.1037/0735-7036.112.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Seeing through sound: Dolphins (Tursiops truncatus) perceive the spatial structure of objects through echolocation.

Abstract: Experiment 1 tested a dolphin (Tursiops truncatus) for cross-modal recognition of 25 unique pairings of 8 familiar, complexly shaped objects, using the senses of echolocation and vision. Cross-modal recognition was errorless or nearly so for 24 of the 25 pairings under both visual to echoic matching (V-E) and echoic to visual matching (E-V). First-trial recognition occurred for 20 pairings under V-E and for 24 under E-V. Echoic decision time under V-E averaged only 1.88 s. Experiment 2 tested 4 new pairs of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…They suggested that echolocation yields a representation of an object that directly corresponds to a vision-derived percept. Additionally, these experiments demonstrate that bottlenose dolphins do not seem to rely on specific details or features of the objects in question, but rather perceive the objects holistically (Herman et al, 1998). Similar findings by Kellogg (1958) and Norris et al (1961) provide evidence that echolocation in bottlenose dolphins seems to replace sight and smell in the water and allow these mammals to encode their surroundings.…”
Section: Echolocationsupporting
confidence: 81%
See 1 more Smart Citation
“…They suggested that echolocation yields a representation of an object that directly corresponds to a vision-derived percept. Additionally, these experiments demonstrate that bottlenose dolphins do not seem to rely on specific details or features of the objects in question, but rather perceive the objects holistically (Herman et al, 1998). Similar findings by Kellogg (1958) and Norris et al (1961) provide evidence that echolocation in bottlenose dolphins seems to replace sight and smell in the water and allow these mammals to encode their surroundings.…”
Section: Echolocationsupporting
confidence: 81%
“…Research has subsequently demonstrated that the amplitude of the emitted sound waves depends on the range to the target, the ambient noise level in the environment, and the difficulty of the task (Au, 1993;Li et al, 2011). Herman et al (1998) used object pairings to determine if the dolphins use vision or echolocation to match novel stimuli. The results indicated that bottlenose dolphins are able to generate a direct shape percept from echolocation, which allows for the accurate matching of various objects.…”
Section: Echolocationmentioning
confidence: 99%
“…Pack, Herman, and their associates (Herman, Pack, & Hoffmann-Kuhnt, 1998;Pack & Herman, 1995;Pack, Herman, Hoffmann-Kuhnt, & Branstetter, 2002) have conducted several cross-modal matching tasks with a sub-adult female dolphin, Elele. The dolphin was trained to match objects intra-modally (sample and choices both presented only visually or only echoically) and cross-modally (visual samples to echoic alternatives; echoic samples to visual alternatives).…”
Section: Extraction Of Object Features Through Echolocationmentioning
confidence: 99%
“…Immediate cross-modal matching with unfamiliar objects (Herman et al, 1998) and unreinforced identity matching across modalities (Harley et al, 2003) indicate that the dolphin extracts object feature information from echoes. However, we do not know which echo characteristics (e.g., frequency, amplitude) allow the dolphin to extract object feature information (e.g., size, shape) or how it works.…”
Section: Extracting Object Features From Echo Featuresmentioning
confidence: 99%
“…A useful analysis of the acoustic scenes, as they are represented in sequences of echoes, requires the identification of the acoustically complex objects surrounding the animals in their natural habitat. Many studies have provided insights into the extraordinary capabilities of echolocating animals in object recognition and classification (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%